Nivel de afrontamiento y grado de estrés de los familiares del paciente hospitalizado en le unidad de cuidado intensivos - Hospital Regional Docente de Trujillo - Rodríguez Llapo, Roxana Gisela (2019)
The present descriptive - correlational research study. It was carried out in the Regional Teaching Hospital of Trujillo during the months November 2016 to January 2017, in order to determine the relationship between the level of coping of the family caregiver and the degree of stress. The sample consisted of 45 relatives who met the criteria for inclusion of the research. For data collection, two instruments were used: a measure of the level of coping of the relative caregiver and a scale to measure the degree of stress, the results were analyzed statistically and presented in statistical tables, single and double entry and analyzed by means of the "Chi Square" criteria independence test that measures the relationship between two variables. After the analysis, the following conclusions were reached: 76.2% of the relatives of the patient hospitalized in the intensive care unit presented a degree of medium stress, 23.8% a high degree of stress; in relation to the level of coping, 53.3% had a high level of coping and 46.7% had a medium level. It was found that there is a relationship between the level of coping and the degree of stress of family members of the hospitalized patient in the intensive care unit, with a chi square value of 5.47 with p = 0.019 being significant.